Climate Adaption for Energy Utilities: Lessons Learned From California's Pioneering Regulatory Actions - Ziaja, Sonya; Chhabra, Mohit (Frontiers in Climate, 2021)
* The regulatory bodies responsible for oversight of investor-owned energy utilities are ill-equipped to regulate climate adaptation in the energy sector; but they may be the only institutions with authority to do so. * In 2018, the California Public Utilities Commission initiated the first quasi-legislative procedure to regulate investor owned energy utilities’ climate adaptation activities. * The Commission’s new rules for climate adaptation offer some general guidance on climate adaptation, and require investor owned utilities to conduct and submit climate vulnerability studies. * Structural limitations, including conflicting interest, capacity of staff, and scope of the problem hampered the success of adaptation regulation, which failed to address fundamental questions about what constitutes adaptive measures.